PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Naris Setyowati; Dinar Dwie Santosa; Turiyah; Ngurah Ayu Nyoman M (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the strategic role of the principal in improving teacher performance in elementary schools. The study uses a qualitative approach through literature studies, this study analyzes relevant theories, government regulations, especially Perdirjen GTK No. 7607/B.B1/HK.03/2023—and findings from previous studies. The role of the principal is discussed based on the EMASLIM framework (Educator, Manager, Administrator, Supervisor, Leader, Innovator, and Motivator). The results of the research reviewed in this study indicate a significant relationship between principal leadership and improved teacher performance. Based on literature studies, the dimensions of the principal's role as an educator and leader have the highest contribution to improving teacher professionalism. Meanwhile, the role of the principal contributes to improving teacher quality and improving teacher performance. Thus, it can be concluded that strengthening the principal's leadership competency is an important key in efforts to improve teacher performance and the quality of education as a whole. The principal needs to act as a visionary, supportive, and collaborative learning leader.